QAUL QADIM DAN QAUL JADID IMAM SYAFIâI: TELAAH FAKTOR SOSIOLOGISNYA - Lahaji, Lahaji; Muhammad, Nova Effenty (IAIN Sultan Amai Gorontalo, 2015)
This paper aims to determine the sociological factors which underlying the birth of the old fatwas (qaul qadim) and the new fatwas of Imam Shafii. This research is a qualitative descriptive with the sociology of Islamic law approach. The results showed that the birth of the old fatwas and the new fatwas of Imam Shafii because the time difference and the case in the area of Baghdad and Egypt when he settled there. The fatwa difference to accommodate legal issues that arise at the moment and this requires ijtihad, so that Islamic law will contribute significantly and functional in anticipation of social dynamics with different complexity of the problems it causes.